Praktek Income Smoothing Ditinjau dari Cash Holding, Bonus Plan, Kepemilikan Institusional dan Profitabilitas - Sari Fadillah; Elvira Luthan (Universitas Muhammadiyah Malang, 2023)
Purpose: This study aims to examine the effect of cash holding, bonus plans, institutional ownership, and profitability on income smoothing in financial sector companies listed on the Indonesia Stock Exchange. Methodology/approach: The research data is sourced from the Annual Report and Share Price Information of Finacial Companies Listed on the IDX (Indonesian Stock Exchange) 2017-2021. The analytical method uses logistic regression by SPSS 26. Findings: The results show that cash holding and bonus plan have no significant effect on income smoothing. Meanwhile, institutional ownership and profitability have signuficant effect on income smoothing Practical and Theoretical contribution/Originality: The implication of this research is expected to help investors and shareholders to understand the factors that can maximize management behavior to do income smoothing on financial statement. In addition, potential investors are expected to be able to use the findings of this study to help them assess the condition of the company before making investment decisions. Novelty of this research is focusing on the financial sector as a sample whereas previous research only focused on the non-financial sector. Research Limitation: Future studies may be useful to use other variables to income smoothing examined to provide a newly additional finding.